Odpowiedź:
1.
h - wysokość trójkąta = √(11² - 7²) = √(121 - 49) = √72 = √(36 * 2) =
= 6√2 [j]
x = √(h² + 3²) = √[(6√2)² + 9] = √(72 + 9) = √81 = 9 [j]
[j] - znaczy właściwa jednostka
2.
h - wysokość = √(7² + 2²) = √(49 + 4) = √53 [j]
(2 + y)² = 9² - h² = 81 - (√53)² = 81 - 53 = 28 [j]
4 + 4y + y² = 28
y² + 4y + 4 - 28 = 0
y² + 4y - 24 = 0
a = 1 , b = 4 , c = - 24
Δ = b² - 4ac = 4² - 4 * 1 * (- 24) = 16 + 96 = 112
√Δ = √112 = √(16 * 7) = 4√7
y₁ = (- b - √Δ)/2a = (- 4 - 4√7)/2 = - 4(1 + √7)/2 = - 2(1 + √7)
y₂ = ( - 4+ 4√7)/2 = 4(√7 -1)/2 = 2(√7 - 1)
Ponieważ y nie może być liczbą ujemną więc y = 2(√7 - 1) [j]